JONKER, FE Inventory of documents - JONKER, FE (ARCA, 2018)
Farmer, Harrismith (1917-1948); Municipality , Harrismith (1948-1958) ; Speculator, Harrismith (1958- ) ; Permits and notice pertaining to rebellion and receipts, membership card and entry form regarding the Ossewa Brandwag
COVERAGE 0.10 metre
Keywords: JONKER, FE; 1914 Rebellion; Ossewa Brandwag